Frequency Regulation of Combined Cycle Power Plants in Local/Autonomous/Isolated Grid Operation Mode - Hasanli, Dashgin (ADA University, 2023)
The frequency of the power supply is one of the most important indicators of the quality of electrical energy. The required frequency values are maintained by automatic and operational frequency control or regulation. Frequency changes usually occur due to some imbalances between the power consumed by loads and the power generated by the power stations and in the event of an imbalance, all frequency regulation systems work to restore the power balance. These mentioned above facts work for overall power system as well as to the power systems in the isolated (islanded) grid operation mode. In the following work the frequency regulation of combined cycle power plants (CCPP) in the isolated grid operation mode has been studied. First of all, some fundamental characteristics of the primary, secondary and tertiary frequency regulation stages in the power system have been provided and then the general aspects of combined cycle power plants and their control mechanisms have been researched. In order to show the importance of CCPPs in Azerbaijan power system, necessary data regarding the installed power capacities and generated electrical energy has been provided. In order to analyze the frequency regulation in CCPP in isolated grid operation mode we have researched for existing mathematical models of these kind of systems. Finally, the Rowen model was selected and implemented in the following work. The simplified mathematical model for simulation purposes of the frequency regulation in isolated grid operation mode using CCPP was developed using MATLAB SIMULINK 2023 software. The results obtained during simulation were very much realistic and then the impact of different unit block in the CCPP system to the frequency regulation has been studied. Finally, the obtained results have been discussed and some ideas for the future work in the area of interest have been given.
Keywords: Frequency regulation--Power systems; Combined cycle power plants (CCPP)--Operation; Isolated power grids--Operation; Power system control--Frequency regulation; Power generation--Azerbaijan; Azerbaijan--Power systems--Frequency regulation; IT and Engineering